What Is World Literature? - Damrosch, David (Book collections on Project MUSE., 2003)
World literature was long defined in North America as an established canon of European masterpieces, but an emerging global perspective has challenged both this European focus and the very category of "the masterpiece." The first book to look broadly at the contemporary scope and purposes of world literature, What is world literature? probes the uses and abuses of world literature in a rapidly changing world. In case studies ranging from the Sumerians to the Aztecs and from medieval mysticism to postmodern metafiction, David Damrosch looks at the ways works change as they move from national to global contexts. Presenting world literature not as a canon of texts but as a mode of circulation and of reading, Damrosch argues that world literature is work that gains in translation. When it is effectively presented, a work of world literature moves into an elliptical space created between the source and receiving cultures, shaped by both but circumscribed by neither alone. Established classics and new discoveries alike participate in this mode of circulation, but they can be seriously mishandled in the process. From the rediscovered Epic of Gilgamesh in the nineteenth century to Rigoberta Mench's writing today, foreign works have often been distorted by the immediate needs of their own editors and translators.